2021
DOI: 10.1098/rstb.2020.0456
|View full text |Cite
|
Sign up to set email alerts
|

Vocal plasticity in harbour seal pups

Abstract: Vocal plasticity can occur in response to environmental and biological factors, including conspecifics' vocalizations and noise. Pinnipeds are one of the few mammalian groups capable of vocal learning, and are therefore relevant to understanding the evolution of vocal plasticity in humans and other animals. Here, we investigate the vocal plasticity of harbour seals ( Phoca vitulina ), a species with vocal learning abilities observed in adulthood but not puppyhood. To evaluate early mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 84 publications
0
23
0
Order By: Relevance
“…As shown here, by testing for allometric relationships between body size and vocal tract structures, one can start to disentangle the respective contributions of vocal anatomy and vocal motor control in shaping acoustic signals. We find that harbour seals are mechanistically constrained by their vocal anatomy, and their large vocal flexibility (Ralls et al, 1985;Borda et al, 2021), which may result in the production of dishonest signals, thus points towards extensive volitional control over their vocalisations. In brief, we provide support for the morphology vs. learning hypothesis, showing however that this relation may be mediated by ontogeny.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…As shown here, by testing for allometric relationships between body size and vocal tract structures, one can start to disentangle the respective contributions of vocal anatomy and vocal motor control in shaping acoustic signals. We find that harbour seals are mechanistically constrained by their vocal anatomy, and their large vocal flexibility (Ralls et al, 1985;Borda et al, 2021), which may result in the production of dishonest signals, thus points towards extensive volitional control over their vocalisations. In brief, we provide support for the morphology vs. learning hypothesis, showing however that this relation may be mediated by ontogeny.…”
Section: Discussionmentioning
confidence: 86%
“…In one special case, a human-raised harbour seal, named Hoover, was found capable of mimicking human speech sounds (Ralls et al, 1985). In a more recent study on harbour seal pups, young animals were found capable of lowering their fundamental frequency (f 0 ) in the presence of background noise (Torres Borda et al, 2021). Do the environmental noise conditions in which vocalisations are produced have a stronger influence on the f 0 values than body size?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining seven contributions in Part 1 are empirical. Torres Borda et al [4] (critical topics (ii) and (iii)) present evidence of the early emergence of vocal plasticity in an aquatic mammal, the infant harbour seal. Their results show that these pinniped pups, known to be capable of vocal learning in adulthood, can already modulate calls in response to noise at one to three weeks of age.…”
Section: Topics and Articlesmentioning
confidence: 99%